Fundamentals of musculoskeletal imaging - McKinnis, Lynn N., 1959-; McKinnis, Lynn N., 1959- (Philadelphia : F.A. Davis, 2021)
"The goal of the is book has always been to serve as the key to the fundamentals of imaging, sufficient for any physical therapist to optimize their interactions with imaging. Despite similar educational preparation, there exists wide variability in a physical therapist's dealings with imaging. Whatever setting you practice in, this book will serve as a primer, a reference, or a decipher of diagnostic imaging to enable you to provide the best care for the patient"--
General principles of musculoskeletal imaging -- Radiologic evaluation, search patterns, and diagnosis -- Radiologic evaluation of fracture -- Computed tomography / Hilmir Agustsson -- Magnetic resonance imaging / Hilmir Agustsson -- Diagnostic ultrasound / Hilmir Agustsson -- Radiologic evaluation of the cervical spine / Sherman Auyeung, Toran D. MacLeod, Rolando T. Lazaro -- Radiologic evaluation of the temporomandibular joint / Hilmir Agustsson -- Radiologic evaluation of the thoracic spine, sternum, and ribs / Sherman Auyeung, Toran D. MacLeod, Rolando T. Lazaro -- The chest radiograph and cardiopulmonary imaging -- Radiologic evaluation of the lumbosacral spine and sacroiliac joints / Lance M. Mabry -- Radiologic evaluation of the pelvis and hip / Mike Rosenthal -- Radiologic evaluation of the knee / Mike Rosenthal -- Radiologic evaluation of the ankle and foot / Mike Rosenthal -- Radiologic evaluation of the shoulder / Kimiko Yamada -- Radiologic evaluation of the elbow / Kimiko Yamada -- Radiologic evaluation of the hand and wrist -- Integration of imaging into physical therapy practice / Richard Cahanin, Troy Burley.
Preceded by Fundamentals of musculoskeletal imaging / Lynn N. McKinnis.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Musculoskeletal Diseases -- diagnostic imaging; Diagnostic Imaging -- methods; Musculoskeletal System -- injuries